Communicative Governance Through the Strategic Role of Cabin Crew in Building Public Trust (Study Ethnography in Hajj Depature 2025) - Helsya Suhesti; Henni Gusfa (Jurnal Komunikasi dan Bisnis, 2025)
This study examines the governance of professional communication through the strategic role of cabin crew in the 2025. Hajj travel involves intense emotions, logistical complexity, and diverse pilgrim, requiring exceptionally high communication standards. Although cabin crew deliver frontline safety and service, they function as strategic agents that embody organizational and governmental integrity, thereby shaping public trust. Using a qualitative case study desgin, data were collected through participant observation on Hajj flights, in-depth interviews with cabin crew and Garuda Indonesia management. Analysis of training documents and on board communication protocols. The study identifies communication strategies, patterns, and content used to manage expectations, provide reassurance, and respond to critical on board situations. Findings show that communicative governance emerges from intensive empathetic, cabin crew empowerment for on decision-making, and coordination action. Communicative governance is structures, strategic communication and coordinating organizational with public to build corporate trust. Trust is sustained through transparent, proactive, and adaptive to the need os the pilgrims’ include spiritual. The study concludes that in complex and sensitive service contexts. frontline strategic agents are central to corporate communication governance and offers a transferable for trust-building in the services industry.